Study of practise of knowledge management in Invest Melaka / ‘Amirul ‘Aizat Abu Bakar - Abu Bakar, ‘Amirul ‘Aizat (Faculty of Business and Management, 2010)
This study explores the practices of knowledge management in Invest Melaka. The main purpose is to identify whether Invest Melaka have practice the knowledge management in Invest Melaka. The study also had been conduct to give guidance for Invest Melaka in order to implement and enhances the knowledge management in the organization. The practices of knowledge management in the organization was identified and measures through questions regarding people, process and IT and technology in knowledge management practices and also the understanding of knowledge management in the organization.